The cold war - Heller, Deane Fons, 1924-; Heller, David, 1922- (Derby, Conn. : Monarch Book, 1962)
Examines the origins and major events of the cold war from the end of World War II to 1965
Keywords: World politics -- 1945 -- Juvenile literature; Cold War -- Juvenile literature